Two new species of the sun-spider genus Gaucha from Argentina and Brazil (Solifugae, Mummuciidae) - Botero-Trujillo, Ricardo; Ott, Ricardo; Mattoni, Camilo I.; Nime, Mónica F.; Ojanguren-Affilastro, Andrés A. (Zootaxa, 2019)
Two new species in the South American sun-spider family Mummuciidae are herein described. Gaucha ramirezi sp. nov. is known from the Chancaní Provincial Park and Forest Reserve, Córdoba province, Argentina, and further reported for a single locality to the northeast, in Santiago del Estero province. The systematic position of this species is uncertain and it is not assigned to any species-group of Gaucha Mello-Leitão, 1924. The other species, Gaucha santana sp. nov., is only known from the Ibirapuitã Environmental Protection Area, in the southern Brazilian state of Rio Grande do Sul, and is a member of the fasciata species-group. With these descriptions, the number of known species of Gaucha is raised to eleven.